Psychological exhaustion among university students (Journal of the College of Basic Education, 2023)
Psychological exhaustion represents the highest levels of psychological stress, and therefore it affects the individual's various relationships, including the individual's social relations and interactions with his colleagues at work, neighbors and friends, and extends to the family. Negativity hinders the individual, which results in his lack of production and withdrawal from the environment in which he works, and the psychological pressures that a person faces today, including the pressures of life that lead to a state of physical, mental, emotional and motivational exhaustion as a result of the continuous increase in fatigue and requirements on the shoulders of the individual and his inability to bear them, especially When ambitions do not match the actual reality that he can actually achieve. In light of the foregoing, the current research seeks to achieve the following goals: